EFEKTIVITAS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM INFOMASI NILAI MAHASISWA - M. Thoha Mahmun (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractIn the Information Age and Globalization, use the manual way to convey the value of student test scores are not appropriate because this method is not effective and efficient.  t is also not consistent with the explanation of article 35 paragraph 1 of Law no. 20 of 2003 on National Education System said that the standard of educational facilities including the use of information technology and communisation (ICT). Therefore, the university should make use of information and communication technology (ICT) in the delivery of value to student test scores. Therefore, universities should utilize information and communication technology (ICT) in the delivery of value to student test scores. By using ICT, the information can be obtained quickly and accurately.There are several options that can be used to convey the value of the test results to students include : using the Internet or SMS Using getway. Both methods are no longer a new technology for campus communities. Kata Kunci : Teknologi Informasi dan Komunikasi, Manajemen Informatika, Sistem Kredit Semester, Efektivitas